Evaluation of Phenotypic Markers for Selection and Identification of Candida dubliniensis - Tintelnot, Kathrin (American Society for Microbiology, 2000)
Candida dubliniensis is often associated with C. albicans in cultures. Easy-to-perform selective isolation procedures for these closely related species do not exist. Therefore, we evaluated previously described discriminatory phenotypic markers for C. dubliniensis. A total of 150 oral rinses from human immunodeficiency virus (HIV)-infected patients were cultured on CHROMagar Candida. Dark green colonies described as being indicative of C. dubliniensis and other green colonies, 170 in total, were isolated. Chlamydospore formation, intracellular β-d-glucosidase activity, ability to grow at 42°C, carbohydrate assimilation pattern obtained by the API ID 32C, and Fourier transform infrared (FT-IR) spectroscopy were used for phenotypic characterization. Sequencing of the 5′ end of the nuclear large-subunit (26S) ribosomal DNA gene was used for definitive species identification for C. dubliniensis. C. dubliniensis was found in 34% of yeast-colonized HIV-infected patients. The color of the colonies on CHROMagar Candida proved to be insufficient for selecting C. dubliniensis, since only 30 of 53 proven C. dubliniensis isolates showed a dark green color in primary cultures. The described typical chlamydospore formation can give only some indication of C. dubliniensis. The assimilation pattern proved to be insufficient to discriminate C. dubliniensis from C. albicans. All C. dubliniensis strains showed no or highly restricted growth at 42°C and a lack of β-d-glucosidase activity. Unfortunately, atypical C. albicans strains can also exhibit these phenotypic traits. FT-IR spectroscopy combined with hierarchical clustering proved to be as reliable as genotyping for discriminating the two species.